2013
DOI: 10.1111/j.1468-2435.2010.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

An Econometric Analysis of The Remittance Determinants Among Ghanaians and Nigerians in The United States, United Kingdom, and Germany

Abstract: This paper examines the determinants of remittance behavior relying on a dataset of migrants living in the United Kingdom, Germany and the United States who remit to Ghana and Nigeria. Controlling for endogeneity of several independent variables, the model measures the effects on the amount sent of the following variables: Home Country (Ghana or Nigeria), Host Country (United States, United Kingdom or Germany), Remittance Fees, Relationship to the Receiver, Purpose of Remittance, Financial Obligations in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
1
26
0
1
Order By: Relevance
“…Ecer and Tompkins () included time abroad and monthly calls home in determining connections to the home country. They included a home mortgage variable to capture financial ties to the host country.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecer and Tompkins () included time abroad and monthly calls home in determining connections to the home country. They included a home mortgage variable to capture financial ties to the host country.…”
Section: Methodsmentioning
confidence: 99%
“…The higher frequency of visits implies a greater attachment to the home country and, hence, a higher level of remittances. Ecer and Tompkins () observed that migrants who called home more often had a positive and significant impact on remittances. Calling home or visiting more frequently is an indicator of a connection to kin back home and, thus, a higher level of remittances is expected.…”
Section: Attachment To Host or Home Countrymentioning
confidence: 99%
“…Proponents of the pessimistic view argue that out-migration negatively influences migrant-sending communities because a large proportion of remittances received by households are used for consumption such as construction of bigger houses and spending on feasts, funerals, weddings, and medical bills rather than on productive investments (Adams, 2011; Massey & Basem, 1992; Brown & Ahlburg, 1999; Seddon, 2004, Hoermann & Kollmair, 2009; Reichert, 1981; de Brauw, 2007; Jokish, 2002; Adhikari, 2001; Rempel & Lobdell, 1978; Koc & Onan, 2004; Oberoi & Singh, 1980; Ecer & Tompkins, 2010). Contrastingly, the proponents of the optimistic view (New Economics of Labor Migration (NELM) theory) argue that there is a positive impact of out-migration on migrant-sending areas, most notably through the remittances migrants send back to their households (Taylor, 1999; Stark and Bloom, 1985; Taylor & Martin, 2001; Stark, 1978; Stark & Levhari, 1982; de Haas, 2007; Dey, 2015).…”
Section: Background and Significancementioning
confidence: 99%
“…For example, Adams (1998) demonstrated that in rural Pakistan, international remittances have a significantly positive effect on the accumulation of irrigated and rain-fed land or productive investment assets and not on the accumulation of non-farm or consumption assets. Oberai and Singh (1980) and Ecer and Tompkins (2010) also find that some amount of remittances is spent on productive investments such as the purchase of land, farm equipment, and raw materials such as seeds and fertilizers for farming. In India, Mohanty, Dubey, and Parida (2014) reported that the remittance-receiving households allocated higher proportion of marginal budget shares on health, education and consumer durables than those of households not receiving remittances.…”
Section: Background and Significancementioning
confidence: 99%
“…altruism, self-interest, and insurance and risk sharing (Agarwal & Horowitz, 2002;Arun & Ulku, 2011;ZaiLiang & Ma, 2013;Ecer & Tompkins, 2013). It is assumed that migrants are concerned about their family members back home.…”
Section: Hypothesis On Destination Specific Remittances Received By Hmentioning
confidence: 99%